Complete mitochondrial genome of the headwater livebearer, Poeciliopsis monacha: the mother of clones. Issue 1 (1st January 2016) - Jeon, Yeon Seon; Johnson, Shannon B.; Won, Yong-Jin; Vrijenhoek, Robert C.
Abstract: The sexually reproducing fish, Poeciliopsis monacha (Actinopterygii, Cyprinodontiformes, Poeciliidae), is the maternal ancestor of six hybrid biotypes that reproduce clonally. The gene content and order of its 16, 818 bp mitochondrial genome is virtually identical with that of other sexually reproducing poeciliid fishes, providing no evidence for a mitochondrial involvement in the origins of all-female reproduction.